Efficacy and safety of perioperative immunotherapy for locally advanced thymic squamous cell carcinoma: a retrospective pilot study - Li, Dong; Zou, Yingbo (Frontiers in Surgery, 2025)
BackgroundThymic squamous cell carcinoma (TSCC), the predominant subtype of thymic carcinoma, is a rare and aggressive malignancy. Although the clinical benefits of perioperative immunochemotherapy for non-small cell lung cancer have been confirmed, its role in TSCC remains unclear. This study was performed to evaluate the efficacy and safety of perioperative immunotherapy for locally advanced TSCC.MethodsThe clinical data of 10 locally advanced TSCC patients treated with perioperative immunotherapy were retrospectively analyzed. All the patients received neoadjuvant PD-1 inhibitors plus platinum-based chemotherapy, followed by surgery and adjuvant immunotherapy. Surgical and pathological outcomes, postoperative complications, treatment-related adverse events (TRAEs), and survival outcomes were all assessed.ResultsAfter neoadjuvant immunotherapy, 60% (6/10) of patients achieved partial response and 40% (4/10) obtained stable disease, with the objective response rate of 60% and disease control rate of 100%. R0 resection was achieved in 80% (8/10) of patients, with 2 achieving complete pathological response. All the patients experienced at least one grade 1–2 TRAEs, but no grade 3–4 TRAEs occurred. The most commonly TRAEs were anorexia (70%) and alopecia (70%), followed by fatigue (60%). During the follow-up of 30 months, only 2 patients were dead, with recurrence-free survival of 17 and 19 months and overall survival of 23 months for both.ConclusionPerioperative immunotherapy exhibits a promising resectable rate in locally advanced TSCC, with a manageable safety profile, although survival benefits have yet to be established. In the future, a prospective randomized controlled trial should be performed to further clarify the role of perioperative immunotherapy for locally advanced TSCC.